Selective CB2 Receptor Agonism Protects Central Neurons from Remote Axotomy-Induced Apoptosis through the PI3K/Akt Pathway - Viscomi, Maria Teresa (J Neurosci, 2009)
Endocannabinoids are neuroprotective in vivo and in vitro, but the mechanisms by which they act are largely unknown. The present study addressed the role of cannabinoid receptors during remote cell death of central neurons in a model that is based on cerebellar lesions. A lesion in one cerebellar hemisphere induced remote cell death and type 2 cannabinoid receptor (CB2R) expression in contralateral precerebellar neurons. Of the selective agonists and antagonists that modulated cannabinoid receptor activity, we found that the CB2R agonist JWH-015 reduced neuronal loss and cytochrome-c release, leading to neurological recovery; these effects were reversed by the selective CB2R antagonist SR144528. Analysis of CB2R-triggered signal transduction demonstrated that in axotomized neurons, CB2R regulated Akt and JNK phosphorylation through a PI3K-dependent pathway, whereas other major signaling routes that are dependent on CB2R, such as ERK1/2 and p38, were not involved. This result was corroborated by the observation that the selective PI3K inhibitor LY294002 blocked the CB2R stimulation effects on neuronal survival as well as Akt and JNK phosphorylation levels. Together, these data demonstrate that axonal damage induces CB2R expression in central neurons and that stimulation of this receptor has a neuroprotective effect that is achieved through PI3K/Akt signaling.